Rendering stories in English from Periya Puranam as a strategy to promote reading skills through Cultural contexts: A study with a group of Undergraduates - Shriganeshan, K. (University of Jaffna, 2023)
Teaching of English as a Second Language is conducted at the Faculties of Arts, Hindu Studies and Visual and Performing Arts of the University of Jaﬀna in various groups. The undergraduates of the respective faculties ﬁnd it diﬃcult to refer booksinEnglishevenafterfollowingaten-yearprogrammeoflearningEnglishatSri Lankan schools.To improve their proﬁciency in English, General English is taught in theFirstyearandEnglishforHumanities,EnglishforSocialSciences,andEnglishfor General Purposes in the Second year and English for Career Development and English forAcademic Purposes in the Third year respectively. However, the students found it diﬃcult to manage their reading comprehension passages based on alien and irrelevant topics. It was also observed that the students were poor in oral and written communication. Therefore, it was proposed to use a set of stories, and culturallyfriendly texts from Periya Puranam in English on the assumption that reading such pieceswouldpromotelanguagelearninginculturalcontexts.Thepaperisconﬁnedto theexperimentalstudyconductedwithagroupofHindustudentsfromtheUniversity of Jaﬀna using questionnaires, interviews with the students, lecturers, and administrators, and diary notes of the researcher. The workshop sessions four in number were conducted at diﬀerent intervals during the three-month study.The study concentrates on how stories from Periya Puranam, a non-native religious text could motivate the learners and analyzes qualitatively the students' task sheets and responsestocheckwiththeirimprovement.Finally,recommendationsaremadeinthe light of the ﬁndings achieved. It has been found out that culturally friendly texts have promoted the students' reading skills with more interest while encouraging other skills.
Keywords: Culturally-friendly texts; Non-native Religious texts; Second language learning; PeriyaPuranam; Undergraduates